(untitled) (Research, Society and Development, 2022)
Malignant hypertension is a term that has been used to describe patients with high blood pressure (BP) and multiple complications (target organ damage) with a poor prognosis. Today, the term hypertensive crisis is used to describe patients who have severe BP elevations as follows: Systolic blood pressure (SBP) greater than 180 mmHg and diastolic blood pressure (DBP) greater than 120 mm Hg. The present study aims to analyze the pathophysiology of malignant hypertension. This is a study with a qualitative approach, where the integrative literature review was adopted, which according to Galvão (2012), is a construction of a broad analysis of the literature with pre-defined steps. Conducted through the Virtual Health Library (BVS) in Pubmed databases, using the crossings of the English descriptors “malignant hypertension”, “diagnosis”. Of the different types of hypertensive emergencies, malignant hypertension (MTH) is characterized by extreme elevations in BP and acute microvascular damage that affects various organs, in particular the retina, brain, and kidneys. HTM is likely to be underdiagnosed, being classified as a hypertensive emergency or unattended for several reasons. Malignant hypertension is a systemic disease that causes severe damage to the brain, heart, kidneys, and eyes. Blockers of the renin-angiotensin system appear to be the mainstay of treatment. Management of the clinical management of hypertension through consensus gained from clinical experience and evidence of inadequate quality is required.